2019
DOI: 10.5551/jat.48181
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Plaque Distribution, and Association between Aortic Plaque and Atherosclerotic Risk Factors: An Aortic Angioscopy Study

Abstract: Aim: Knowledge of subclinical plaque morphology and plaque distribution in the aorta in vivo remains unclear. This study aimed to increase the body of knowledge in this area.Methods: We enrolled 37 consecutive patients with stable angina pectoris patients who underwent non-obstructive angioscopy for both the coronary artery and aorta immediately after percutaneous coronary intervention. We evaluated the presence of aortic plaques and the distribution of plaque instability. Patients were allocated into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…First, we introduced TEE examination for 71.6% of continuous cases. The patients in the group who did not undergo TEE were significantly older (82.9 9.5 years vs 75.6 9.4 years, P 0.0001), had a lower prevalence of hypertension (66.7% vs 84.0%, P 0.05), predominantly female (64.3 % vs 30.2 %, P 0.0001), had a higher prevalence of chronic AF (64.3 % vs 40.6 %, P significantly associated with vulnerable plaques, such as intense yellow plaques, ruptured plaques, and thrombi 20) . Taken together with our results, these data suggest that diabetes mellitus is an important predictor of aortic arch atherosclerosis in patients with acute ischemic stroke who have AF.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…First, we introduced TEE examination for 71.6% of continuous cases. The patients in the group who did not undergo TEE were significantly older (82.9 9.5 years vs 75.6 9.4 years, P 0.0001), had a lower prevalence of hypertension (66.7% vs 84.0%, P 0.05), predominantly female (64.3 % vs 30.2 %, P 0.0001), had a higher prevalence of chronic AF (64.3 % vs 40.6 %, P significantly associated with vulnerable plaques, such as intense yellow plaques, ruptured plaques, and thrombi 20) . Taken together with our results, these data suggest that diabetes mellitus is an important predictor of aortic arch atherosclerosis in patients with acute ischemic stroke who have AF.…”
Section: Discussionmentioning
confidence: 94%
“…Further, MRI based plaque imaging showed that type 2 diabetes was significantly associated with the presence of vulnerable carotid plaques, independent of the degree of stenosis 19) . Another study showed that the presence of diabetes was an independent risk factor for vulnerable aortic plaque burden, as evaluated by aortic angioscopy 20) . They evaluated the presence of aortic plaques and the distribution of plaque instability in patients with coronary artery disease, and found that diabetes mellitus and peripheral arterial disease were 12.4, 95%CI: 2.6-59.3, P 0.01).…”
Section: Association Between Vascular Risk Factors and Presence Of Camentioning
confidence: 99%
“…Various types of plaques and injuries detected using NOGA have been reported in aorta [3][4][5][6][8][9][10][11][12][13][14][15] (Table 1). The terms of angioscopic findings are going to be standardized [16].…”
Section: Spontaneous Ruptured Aortic Plaques and Injuriesmentioning
confidence: 99%
“…Various types of SRAPs have been detected ( Fig. 1) 1,12,13,[20][21][22][23][24] . The normal aortic intima is white with a smooth surface ( Fig.…”
Section: Non-obstructive General Angioscopymentioning
confidence: 99%
“…Initially, the distribution of aortic SRAPs and aortic injuries were ─ 63 ─ reported 12,24) . SRAPs are dominant in the infrarenal abdominal artery, suprarenal abdominal artery, and aortic arch.…”
Section: Aortic Angioscopy In Clinical Cardiologymentioning
confidence: 99%